Investigating the dimensionality of Organisational Citizenship Behaviour from Islamic Perspective (OCBIP): empirical analysis of business organisations in South East Asia - Naail Mohd., Kamil; Sulaiman, Mohamed; Osman-Gani, Aahad M.; Khaliq, Ahmad (Asian Academy of Management and Penerbit Universiti Sains Malaysia, 2014)
ABSTRACT: Although Organisational Citizenship Behaviour (OCB) emanating from the Western value system has received enormous attention by researchers, OCB from the Islamic perspective (OCBIP) has not been much explored. This empirical study attempts to enrich the understanding of the OCB phenomenon from Islamic management perspective. A survey of 405 Muslim employees in business organisations in Malaysia was drawn for the study. The construct validity of OCBIP via Chartered Financial Analyst (CFA) led to the major finding; the OCBIP measurement model in the business organisational context is explained by four components; Altruism, Civic virtue, Advocating high moral standards and Removal of harm.